CLINICAL AND THERAPEUTIC CONSIDERATIONS IN LUDWIG ANGINA - Mihaela Cătălina Luca; Carmen Dorobăţ; Florin Roşu; Radu Băiceanu; Andrei Luca (Romanian Society of Oral Rehabilitation, 2014)
This study has the purpose to analyze the clinical, biological and therapeutically aspects, together with the evolution under therapy in Ludwig s angina and the factors who determined the appearence of this very severe disease . The retrospective study was done on a group of 5 adults patients with Ludwigʼs angina, admitted in the Clinic of Infectious Diseases of Iasi, during 2009-2013. All the patients presented stomatological records or angina, that became the portal of entry. The clinical manifestations of the onset were: high fever, local pains, trismus and regional painful tumefaction, or dysphagya and dyspneea. The diagnosis confirmation was realized through bacteriologic exams and the treatment consists in: antibiotherapy associated with surgical drainage, soft tissue decompression, local periodontal therapy of the primary focus and corresponding pathogenic therapy. The response of healing was favorable in all 5 cases. Conclusions: Ludwig angina represents a very severe infection through its systemic potential, the etiologic and anatomic context; this allows the spread of the infection in the mediastin, with direct effects on the respiratory and cardiac functions.